Integration of biomasses gasification and renewable-energies-driven water electrolysis for methane production. (1st September 2021) - Bareschino, P.; Mancusi, E.; Tregambi, C.; Pepe, F.; Urciuolo, M.; Brachi, P.; Ruoppolo, G.
Abstract: In this work, an innovative process layout for methane production is proposed and investigated with the aim to promote the integration of renewable energies chemical storage via hydrogen production by water electrolysis and biomass gasification. The core of the proposed layout is the integration between an experimental fluidized bed gasification system, fed with spruce wood pellets and using Fe/Al2 O3 catalyst, and a conceptual methanation unit. This latter was modelled as a series of adiabatic fixed bed reactors with inter-cooling, water condensation at the exit of each reactor, and product recycle. The performance of the methanation system was evaluated by considering that the product stream coming from the gasifier system reacts, after purification and mixing with pure hydrogen coming from an electrolysis cells array, over Ni supported on alumina catalyst. The number of electrolysis cells to be stacked in the hydrogen production unit was evaluated by considering that a constant H2 production able to reach 7:1:1H2 :CO:CO2 ratio at the inlet of the methanation unit should be attained. Highlights: Adding steam to air as gasification agent enhances the syngas H2 :CO ratio. Steam-and-air gasification lowers the H2 request from water electrolysis. High CO and CO2 conversions are achieved in a multistage adiabatic methanation unit. Syngas to methane could be a viable answer for renewable energies chemical storage.